Future trends in morbid obesity in England, Scotland, and Wales: a modelling projection study. (November 2016) - Keaver, Laura; Webber, Laura
Abstract: Background: The prevalence of morbid obesity is increasing worldwide, with numbers doubling in the past 20 years. Morbid obesity (body-mass index [BMI] ≥40 kg/m 2 ) is associated with a high risk of chronic disease, such as type 2 diabetes, coronary heart disease, stroke, mental illness, and some cancers, and increased all-cause mortality rates. In addition, individuals with morbid obesity have more complex health issues and challenges in the health-care system than do those with a lower BMI. A recent global study reported a prevalence range from less than 0·1% in Chinese women to 23·1% in American women. Morbid obesity accounts for 24–35% of all obesity-related costs, presenting a substantial burden on the economy and health service. We aimed to project trends in morbid obesity to 2035 in adults in England, Scotland, and Wales. Methods: Morbid obesity rates for the three countries were obtained from the Health Survey for England (1993–2015) and Welsh Health Survey (2004–14) through the UK data service online resource and from the Scottish Health Survey team directly (2003, 2008–14). Rates were determined for men and women aged 16 and older separately (in 5 year age-groups). A multivariate non-linear regression was fitted to the data to project BMI trends. Building on previous models used by the UK Health Forum, we used BMI prevalence data, with age and sex as covariates. Validation was not done for this study, but has been done in earlier work with the Foresight study. Findings: Morbid obesity prevalence is projected to vary from 4% (in Scottish men aged 16–24 years old) to 54% (in English men aged 75 and older) by 2035. England and Wales are projected to have higher rates of morbid obesity in men than in women whereas the opposite is true of Scotland. Of the three countries, Wales is projected to have the highest levels of morbid obesity. Additional work is looking at population data. Interpretation: The prevalence of morbid obesity is set to increase to 2035 across England, Scotland, and Wales. This increase will have serious health and financial implications for the health service and population. The next stage will be to run a microsimulation to test the impact of morbid obesity on future disease burden. Funding: None.